The debate: Treatment after the first seizure-The PRO - Olmes, David G.; Hamer, Hajo (Seizure-European Journal of Epilepsy, 2017)
According to current diagnosis criteria, first seizures constitute beginning epilepsy when they carry recurrence risks of >=60% over the next 10 years. This is frequently the case and warrants AED treatment. Evidence argues against deferring treatment when provoking factors such as sleep deprivation are reported. There are several characteristics of first seizures which markedly increase recurrence risk but not clearly beyond 60%. This includes status epilepticus or seizure flurries at first manifestation or focal semiology indicating focal epilepsy. In this situation, there are still various medical, social and individual aspects supporting early initiation of AED. Modern AED allow this safely and at low dosages.
EVALuna2:22486